Intracameral SF6 for Detachment of Descemet's Membrane: a post-surgical complication of Cataract Surgery - Tello Arquíñego, Johans Neil (2024)
Descemet's Membrane Detachment (DMD) is a widely described complication that originates during or after intraocular procedures such as cataract surgeries or trabeculectomies, presenting centrally, peripherally, or combined, and in many cases, it resolves itself. spontaneous. When the detachment occurs intraoperatively and is treated early, the results are mostly satisfactory; however, when the diagnosis is late, the visual prognosis can be reserved. The clinical case of an 83-year-old patient, who underwent phacoemulsification surgery without complications, who presented persistent corneal edema without improvement in visual acuity (VA) in the postoperative period, was performed. Anterior Segment Optical Coherence Tomography was performed. (AS-OCT) showing a DMD being treated with 20% sulfur hexafluoro (SF6). The corneal edema resolved, presenting a best corrected visual acuity (BCVA) of 20/30 at 2 weeks. Keywords: Descemet membrane detachment, cataract surgery, corneal edema.